Pengaruh Variasi Penempatan Kutub Medan Magnet pada Pengurangan Kadar CaCO3 dalam Air: Triswantoro Putro, Endarko - Triswantoro Putro, Triswantoro Putro; Endarko, Endarko (Jurnal Fisika dan Aplikasinya, 2025)
Design and fabrication of precipitation system of calcium carbonate (CaCO3) in water using magnetic field methods have been successfully carried out. Magnetic field governed to precipitate calcium carbonate in water. The study was investigated the polar position of the magnetic field. Two positions of magnetic field were tested namely the system with alternated polar magnetics and the system without inversion of the polar magnetics. The results showed that treatment of the magnetic field poles are arranged in series in the sample solution with a concentration of 1040 g CaCO3/L in water to give maximum reduction percentage of 30.55% for 80 minutes. While the preparation of magnetic poles in parallel, obtained a maximum of 57.69% reduction for 120 minutes. pH and conductivity of water samples in the measuring solution and showed a decrease in pH and conductivity after water samples were processed for 120 minutes, respectively for 23.43% and 69.23%.